Cross-protection induced by VA-MENGOC-BC® vaccine - Rolando Felipe Ochoa-Azze (Taylor & Francis Group, 2018)
I would like to comment on the article "Commentary: Impact of meningococcal group B OMV vaccines, beyond their brief", DOI: 10.1080/21645515.2017.1381810. The author states that meningococcal group B OMVs vaccines -such as VA-MENGOC-BC®- may induce moderate protection against Neisseria gonorrhoeae. I agree. However, the author states that "there was no evidence of effectiveness in the younger children." The effectiveness of VA-MENGOC-BC® in heterologous contexts has been higher than 80% in individuals older than 4 years old, but the effectiveness in younger children should not be undervalued; it has usually been higher than 60%, and results markedly higher when evaluated based on mortality rates. There is strong evidence that VA-MENGOC-BC® may induce cross-protection against heterologous N. meningitidis strains and N. gonorrhoeae.